Increasing entrepreneurial intention: effective entrepreneurship course characteristics. (1st January 2011) - Mueller, Susan
Ajzen's model of planned behaviour was used to measure the impact of specific entrepreneurship course characteristics on entrepreneurial intention. Course characteristics with a hypothesised positive influence on entrepreneurial intention were identified through literature research and an exploratory study. The hypotheses were tested with a quantitative study which was designed as an ex ante/ex post measurement. Course elements such as business planning activities, role models, student-oriented teaching and feedback processes are efficient components to increase entrepreneurial intention through its antecedents.